2007
DOI: 10.2527/jas.2006-735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winter stocker growth rate and finishing system on: I. Animal performance and carcass characteristics1,2

Abstract: Angus-crossbred steers (n = 216) were used in a 3-yr study to assess the effects of winter stocker growth rate and finishing system on finishing performance and carcass characteristics. During winter months (December to April) steers were randomly allotted to 3 stocker growth rates: low (0.23 kg x d(-1)), medium (0.45 kg x d(-1)), or high (0.68 kg x d(-1)). Upon completion of the winter phase, steers were randomly allotted within each stocker treatment to a corn silage-concentrate or pasture finishing system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 12 publications
5
31
3
1
Order By: Relevance
“…Mean LM area was 59 or 60 cm^ for the 3 groups, and mean fat thickness over the 12th rib ranged from 0.62 cm (CONT) to 0.74 cm (CSBM). The LM area was smaller for these steers than the LM area observed for steers finished on pasture and slaughtered at close to the same age (Neel et al, 2007), yet HCW and fat thickness over the 12th rib were less for the steers studied by Neel et al (2007), possibly because they were Angus-crossbred steers rather than full-blood Angus. Mean USDA yield grade was 2.9 for both supplemented groups and was 2.6 for CONT, which was greater than the yield grade of 1.6 reported by Neel et al (2007) for their pasture-finished steers.…”
Section: Carcass Characteristicscontrasting
confidence: 52%
See 1 more Smart Citation
“…Mean LM area was 59 or 60 cm^ for the 3 groups, and mean fat thickness over the 12th rib ranged from 0.62 cm (CONT) to 0.74 cm (CSBM). The LM area was smaller for these steers than the LM area observed for steers finished on pasture and slaughtered at close to the same age (Neel et al, 2007), yet HCW and fat thickness over the 12th rib were less for the steers studied by Neel et al (2007), possibly because they were Angus-crossbred steers rather than full-blood Angus. Mean USDA yield grade was 2.9 for both supplemented groups and was 2.6 for CONT, which was greater than the yield grade of 1.6 reported by Neel et al (2007) for their pasture-finished steers.…”
Section: Carcass Characteristicscontrasting
confidence: 52%
“…The LM area was smaller for these steers than the LM area observed for steers finished on pasture and slaughtered at close to the same age (Neel et al, 2007), yet HCW and fat thickness over the 12th rib were less for the steers studied by Neel et al (2007), possibly because they were Angus-crossbred steers rather than full-blood Angus. Mean USDA yield grade was 2.9 for both supplemented groups and was 2.6 for CONT, which was greater than the yield grade of 1.6 reported by Neel et al (2007) for their pasture-finished steers. Mean marbhng scores for the 3 groups of steers did not differ (P = 0.91), and not surprisingly, were considerably less than marbling scores for the beef heifers fed flaxseed and flnished on concentrate reported by Maddock et al (2006a).…”
Section: Carcass Characteristicscontrasting
confidence: 52%
“…Our research found that backgrounding treatment had no effect on DMI, ADG, or G:F during the finishing period (P ≥ 0.121). When comparing low, medium, and high rates of winter BW gain during the backgrounding period, Neel et al (2007) reported that cattle fed to achieve a low rate of BW gain during backgrounding had the greatest ADG during the finishing period, whereas cattle fed to achieve a high rate of BW gain had the least ADG during the finishing period. Coleman et al (1995) reported initial ADG increased in the feedlot with steers grown on a slower rate of BW gain (silagebased diet) compared with steers grown at a greater rate of BW gain (grain-based diet).…”
Section: Finishing Performancementioning
confidence: 99%
“…Several have assessed various management systems or quality of forages on subsequent gain during the finishing period and effects on carcass traits (3,6,7,9,10). Neel et al (8) wintered stockers in drylot with restricted rations to create three gain categories, and concluded that stocker growth affected finishing performance and carcass quality. The objectives of this study were to quantify the effects of graded weight gain from winter annual pastures on subsequent feedlot performance, overall liveweight growth rate, and carcass traits of beef cattle.…”
Section: Introductionmentioning
confidence: 99%